Tiga Aspek Preferensi Pengguna Coworking Space dengan Pendekatan Stated Preference: Desain, Pelayanan, dan Kualitas Lingkungan Ruang Dalam - Pamela, Sofia; Kusuma, Hanson E; Safira, Annisa (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2021)
The growing number of Coworking Space is one of the phenomena that occurred in the 4.0 industrial era. This is due to changes in work activity model that can be done anywhere with simple devices. The study aims to see the preference of users towards Coworking Space. The research method is qualitative using a grounded theory approach. Data collection was carried out by distributing online questionnaires with open-ended questions and a non-random sampling technique. Data were analyzed using content analysis method, namely open coding. The preference model used is stated preference. The result of the analysis shows that there are three aspects of Coworking Space preferences. They are Design, Service, and Indoor Environmental Quality. The design aspects consist of furniture and interior design, visual comfort, atmosphere, and privacy. Service aspects include facilities, services, accessibility, and social interactions. Indoor environmental Quality is a group of categories of tranquillity, coolness, and health.